ʺInclusive environment of general secondary educational institution: theoretical foundationsʺ - Grianyk, D. (Problems of Engineer-Pedagogical Education, 2024)
The introduction of an inclusive form of education in a general secondary education institution involves the organisation of an inclusive educational environment and management of its development with the involvement of all participants - teachers, parents, and students. This fact leads to increased attention of scholars to the peculiarities of organising an inclusive environment in a general secondary education institution, which indicates the relevance of this issue. The purpose of the article is to study the theoretical basis for organising an inclusive environment in a general secondary education institution. The results of the analysis of the theoretical foundations of inclusive education made it possible to state the development of various scientific approaches to determining the features of the implementation and functioning of inclusive education, as well as to identify the main areas of research of scientists in the field of inclusive education: organisational and pedagogical aspects of the problem of creating an inclusive environment; the role of the teacher of an inclusive institution; general features of psychological and pedagogical support and the work of the psychological and pedagogical support team; implementation of other Also, the analysis of scientific sources shows that the goal common to all the approaches and directions under consideration is to ensure equal access to quality educational services for all children, regardless of their characteristics. It has been determined that the incubative environment of general secondary education institutions, in turn, should contribute to ensuring equal access to quality education and the development of important skills that will help students integrate into society. However, there are still many issues related to the organisation of an inclusive environment in general secondary education that require detailed consideration: teacher training for work in an inclusive environment, specifics of organising inclusive education in a distance format, ways to modify and adapt educational material, specifics of adapting the system of assessment of students with special educational needs in an inclusive education environment. The specificity of these issues determines further prospects for research in the field of inclusive education.